Policy evaluation on poverty alleviation of the Gana resettlement and integrated development (GRID) project in Sabah / Oliverra M. Lim - M. Lim, Oliverra (2022)
This study focuses on Gana Resettlement and Integrated Development (GRID) Project as a model for poverty alleviation in Kota Marudu, Sabah. GRID is also known as the Community-Based Project of Lingkabau Forest Reserve (LFR). This study has two objectives; (i) to examine the different dimensions of poverty that exist in Gana and, (ii) to evaluate to what extent the initiatives under the GRID Project can alleviate poverty among the Gana communities. The GRID Project was placed under Sabah Forestry Department (SFD) and focused on forest conservation and improving the standards of living among the communities. This study is quantitative. It is a survey using a standardized questionnaire by the International Fund for Agricultural (IFAD): Multidimensional Poverty Assessment Tools (MPAT). A total of 242 respondents participated in the distribution of the MPAT Households Survey and the MPAT Village Survey consists of 73 questions covering 10 components and 31 subcomponents. The findings indicate that the dimensions of poverty still existing in Gana after the GRID Project were Domestic Water Supply, Farm Assets and Non-farm assets, three out of 10 MPAT components. However, the GRID Project had contributed to significant changes among the communities in Kg. Gana with improved basic infrastructure, better access to education, healthcare, job opportunity and other basic amenities and services since 1998. This study argues that the GRID Project had been successful in alleviating poverty in Kg. Gana but certain dimensions under MPAT still needed improvements notably the three components under poverty identified above.